Effect of Organic Fertilizers, Mycorrhiza and Tillage on Yield and Uptake of Nitrogen and Phosphorus in Seed, Leaves and Soil under Maize Cultivation - Alireza Feilinezhad; Mohammad Mirzaeiheydari; Farzad Babae; Abbas Maleki; Mahmood Rostami nia (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
The present experiment was conducted to investigate the effect of tillage, organic fertilizers and mycorrhiza on quantitative traits and nutrient uptake in maize. The experiment was performed as a split plot with 4 replications in a randomized complete block design in August of the crop year 2017 and 2018 in Ivan city in Ilam province. Tillage at 3 levels (no tillage, tillage to a depth of 10 cm and tillage to a depth of 30 cm), organic fertilizer at 3 levels (no use, vermicompost 30 tons per hectare and bovine manure 30 tons per hectare) and mycorrhizal fungus Glomus mosseae and it was by soil inoculation method (consumption and non-consumption). In a minimal tillage system, seed yield was 7053.2 kg ha-1, an increase of 21% compared to the least amount of tillage-free treatment. In the minimum tillage system and the consumption of cow manure, the highest grain yield was obtained in the amount of 8198.2 kg ha-1. The interaction of mycorrhizae and tillage on grain yield was significant. In the case of minimal tillage and mycorrhizae, the maximum grain yield was707.1 kg ha-1, which was significantly different from the treatment without tillage and deep in both mycorrhizal and non-amycorrhizal states. According to the results obtained in this study, it was found that soil application at least relative to the deep system has increased plant yield.